Les études caryolytiques de trois espèce de famille de liliacées (A.cepa L ,A.sativum L, A.porrum L) - KADDOUR BEN CHRIF, Rekaya; MERAH, Yamina (My University, 2021)
Our work is based on the study of the karyotype of the following three species, Allium cepa. Allium sativum. Allium porrum of the Lilacs species, to obtain tropical plates. We first dealt with a comprehensive study of this type in terms of definition and classification, and a special study for each of these three species, as we have a microscopic study. In order to identify the chromosomes of this species, we learned about their number, type and shape with the effect of colchicines which block metaphase mitosis of young roots and the fish technique, which we have learned by studying their properties and how they work to show the chromosome. It was found that the diploid chromosome number (Alluim sativum, alluim cepa) is equal to (2N=16), compared to the diploid number of chromosome alluim porrum equal to (2N=32).
Keywords: Lilacs- karyotype- allium - Mitosis –cytogenetic.